Effect of Carotene and Lycopene on the Risk of Prostate Cancer: A Systematic Review and Dose-Response Meta-Analysis of Observational Studies. - Yulan Wang; Ran Cui; Yuanyuan Xiao; Juemin Fang; Qing Xu (PLoS ONE, 2015)
Background Many epidemiologic studies have investigated the association between carotenoids intake and risk of Prostate cancer (PCa). However, results have been inconclusive. Methods We conducted a systematic review and dose-response meta-analysis of dietary intake or blood concentrations of carotenoids in relation to PCa risk. We summarized the data from 34 eligible studies (10 cohort, 11 nested case-control and 13 case-control studies) and estimated summary Risk Ratios (RRs) and 95% confidence intervals (CIs) using random-effects models. Results Neither dietary β-carotene intake nor its blood levels was associated with reduced PCa risk. Dietary α-carotene intake and lycopene consumption (both dietary intake and its blood levels) were all associated with reduced risk of PCa (RR for dietary α-carotene intake: 0.87, 95%CI: 0.76-0.99; RR for dietary lycopene intake: 0.86, 95%CI: 0.75-0.98; RR for blood lycopene levels: 0.81, 95%CI: 0.69-0.96). However, neither blood α-carotene levels nor blood lycopene levels could reduce the risk of advanced PCa. Dose-response analysis indicated that risk of PCa was reduced by 2% per 0.2mg/day (95%CI: 0.96-0.99) increment of dietary α-carotene intake or 3% per 1mg/day (95%CI: 0.94-0.99) increment of dietary lycopene intake. Conclusions α-carotene and lycopene, but not β-carotene, were inversely associated with the risk of PCa. However, both α-carotene and lycopene could not lower the risk of advanced PCa.